(3GdeMGSHI GdhWfjI (B:s (3fXGe GdMSGHGJ GdEbJUGOjI GdLRGFQjI f(B.(3M(B.(3E(B.(3L eOYe HYOO ef GdCeKdI hGdJeGQjf GdeMdhdI (B/s - (3bGSe, bGOIs; (3bOj, YHO GdeLjO s ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2002)
(3GdeMGSHI GdhWfjI(B- (3GdYQV GdYGe dfXGe GdMSGHGJ GdEbJUGOjI GdLRGFQjI (B-(3fXGe GdeMGSHI GdhWfjI(B.s
Keywords: (3GdeMGSHIs; (3GdeMGSHI GdYGeIs